Стратегія управління фінансовим станом підприємства (на прикладі ТзОВ "Львівський вентиляційний завод") - Боберський, Ростислав Іванович; Boberskyi, Rostyslav Ivanovych (Національний університет "Львівська політехніка", 2024)
Дипломна робота формування присвячена актуальному питанню та реалізації ефективної стратегії управління фінансовим станом підприємства в умовах сучасного економічного середовища. Особлива увага приділена дослідженню фінансового стану ТОВ «Львівський вентиляційний завод» — підприємства, що функціонує в галузі виробництва промислового вентиляційного та холодильного устаткування, що намагається активно розширити свою діяльність, проте стикається з викликами нестабільного ринку, конкуренції та зростання витрат на виробництво. Об’єктом підприємства.Предметом дослідження є стратегія управління фінансовим станом дослідження є процес управління фінансовим станом підприємства, рентабельністю. його стійкістю, структурою капіталу, ліквідністю та Метою роботи є дослідження теоретичних та практичних аспектів управління фінансовим станом підприємства з метою виявлення напрямів його вдосконалення на прикладі ТОВ «Львівський вентиляційний завод. У першому розділі досліджено теоретичні основи формування фінансової стратегії підприємства. Вагомий внесок у вивчення фінансової стратегії та фінансової політики зробили М. Портер, В. П. Мартиненко, М. В. Левіна, Т. С. Карпова, І. С. Лапіна, Н. Захарова, В. О. Романишин та інші. Науковці досліджували вплив чинникі макро- і мікросередовища на процес визначення і формування довгострокових фінансових цілей. Увага зосереджена на алгоритмі розробки фінансової стратегії, методах гнучкого бюджету, управління витратами задля підвищення ефективності господарювання [1]. Поняття фінансової стратегії як системи довгострокових цілей і засобів їх досягнення у фінансовій площині широко розкривається в роботах Г. К. Савицької, яка підкреслює, що фінансова стратегія визначає загальну логіку управління фінансовими ресурсами підприємства і формує основу для прийняття поточних фінансових рішень [2]. Також опрацьовано роботи: М. Друкера, Л. П. Прокопенка, Н. Г. Чухрай, В. М. Опарін. Г. Щвиданенко.Також було проведено горизонтальний і вертикальний аналіз фінансових показників підприємства. Побудовано матрицю SPACE, яка допомогла оцінити фінансовий стан, конкурентноспроможність, стабільність і галузеві перспективи. Виявлено основні проблеми: зниження рівня платоспроможності, зростання кредиторської заборгованості, нестача власного капіталу. Другий розділ присвячений аналізу фінансового стану ТОВ «Львівський вентиляційний завод», за допомогою SWOT-аналізу. Цей аналіз дозволив виявити сильні та слабкі сторони, можливості й загрози зовнішнього середовища підприємства, які можуть вплинути на його розвиток. Також у розділі проведене прогнозування фінансових показників підприємства. При прогнозуванні окремих фінансових показників використано метод екстраполяції. У розділі також наведене індивідуальне наукове дослідження. Мета статті полягає в аналізі поняття «фінансовий ризик», а також виокремлення відповідних негативних моментів у фінансовій системі України в період військової агресії та пошук можливих шляхів зменшення їхнього впливу на економіку держави в цілому. У третьому розділі розроблено стратегічні заходи з удосконалення управління фінансовим станом підприємства. Оптимізація структури капіталу є ключовим елементом фінансового управління, оскільки вона безпосередньо впливає на здатність підприємства забезпечувати фінансову стійкість, прибутковість і конкурентноспроможність. Запропоновано впровадження комплексної фінансової стратегії, що включає: оптимізацію структури капіталу, підвищення рентабельності за рахунок зниження витрат, удосконалення управління дебіторською та кредиторською заборгованістю, а також покращення системи фінансового планування та контролю. Застосовано методи фінансового прогнозування, які дозволили моделювати очікувані результати реалізації запропонованих заходів у середньостроковій перспективі. Практичне значення роботи полягає в можливості використання розроблених рекомендацій для підвищення ефективності фінансового управління на ТОВ «Львівський вентиляційний завод», що є запорукою стабільного функціонування підприємства в умовах конкуренції та ринкових ризиків.

The thesis is devoted to the topical issue of forming and implementing an effective strategy for managing the financial condition of an enterprise in the conditions of the modern economic environment. Particular attention is paid to the study of the financial condition of LLC "Lviv Ventilation Plant" - an enterprise operating in the field of industrial ventilation and refrigeration equipment production, which is trying to actively expand its activities, but is faced with the challenges of an unstable market, competition and increasing production costs. The object of the study is the strategy for managing the financial condition of an enterprise. The subject of the study is the process of managing the financial condition of an enterprise, its stability, capital structure, liquidity and profitability. The purpose of the work is to study the theoretical and practical aspects of managing the financial condition of an enterprise in order to identify areas for its improvement using the example of LLC "Lviv Ventilation Plant". The first section examines the theoretical foundations of the formation of the financial strategy of an enterprise. A significant contribution to the study of financial strategy and financial policy was made by M. Porter, V. P. Martynenko, M. V. Levina, T. S. Karpova, I. S. Lapina, N. Zakharova, V. O. Romanyshyn and others. Scientists studied the influence of macro- and microenvironmental factors on the process of determining and forming long-term financial goals. Attention is focused on the algorithm for developing a financial strategy, flexible budget methods, cost management to increase business efficiency [1]. The concept of financial strategy as a system of long-term goals and means of achieving them in the financial sphere is widely disclosed in the works of G. K. Savitskaya, who emphasizes that the financial strategy determines the general logic of managing the financial resources of the enterprise and forms the basis for making current financial decisions [2]. Also worked on the works of: M. Drucker, L. P. Prokopenko, N. G. Chukhrai, V. M. Oparin. G. Shchvydanenko. A horizontal and vertical analysis of the financial indicators of the enterprise was also carried out. The SPACE matrix was built, which helped to assess the financial condition, competitiveness, stability and industry prospects. The main problems were identified: a decrease in the level of solvency, an increase in accounts payable, a lack of equity. The second section is devoted to the analysis of the financial condition of LLC "Lviv Ventilation Plant" using SWOT analysis. This analysis allowed to identify the strengths and weaknesses, opportunities and threats of the external environment of the enterprise, which may affect its development. The section also provides a forecast of the financial indicators of the enterprise. When forecasting individual financial indicators, the extrapolation method was used. The section also presents an individual scientific study. The purpose of the article is to analyze the concept of "financial risk", as well as to identify the relevant negative aspects in the financial system of Ukraine during the period of military aggression and to find possible ways to reduce their impact on the economy of the state as a whole. In the third section, strategic measures are developed to improve the management of the financial condition of the enterprise. Optimization of the capital structure is a key element of financial management, since it directly affects the ability of the enterprise to ensure financial stability, profitability and competitiveness. The implementation of a comprehensive financial strategy is proposed, which includes: optimization of the capital structure, increasing profitability by reducing costs, improving the management of receivables and payables, as well as improving the financial planning and control system. Financial forecasting methods are used, which allowed modeling the expected results of the implementation of the proposed measures in the medium term. The practical significance of the work lies in the possibility of using the developed recommendations to improve the efficiency of financial management at LLC "Lviv Ventilation Plant", which is the key to the stable functioning of the enterprise in conditions of competition and market risks.
Strategy for managing the financial condition of an enterprise (using the example of LLC "Lviv Ventilation Plant")
Keywords: 3.072.00.00; фінансовий стан; стратегія управління; фінансовий аналіз; вентиляційне обладнання; підприємство; фінансова стійкість; financial condition; management strategy; financial analysis; ventilation equipment; enterprise; financial stability List of used literature sources; 1. Buchko T. Strategic management of enterprise finances. / Buchko T.; Radynskyi - Material of the XI International Scientific and Practical Conference / [Electronic resource] - Access mode: https://elartu.tntu.edu.ua/bitstream/lib/42940/2/MNPK_2023_Buchcko_TStrategic_management_of_104-105.pdf 2. Drabovskyi A.G. Innovative strategies for managing organizations in the context of digital transformation / Drabovskyi A.G. - Effective economy - No. 4 - 2025 3. Laktionova O. A. Financial risk management: a textbook. / Laktionova O. A. - Vinnytsia: DonNU named after Vasyl Stus - 2020. 256 p. 4.Levchenko; V. I. Economic modeling of financial strategies / V. I. Levchenko. – Kharkiv: KhDU; 2021. – 185 p. 5.Lyashenko; M. O. Modeling the financial state of enterprises / M. O. Lyashenko. – Kyiv: Publishing house "Disa"; 2020. – 210 p. 6.Martynenko V.P. Conceptual aspects of the financial strategy of an enterprise / Martynenko V.P. - Economic Bulletin of NTUU "KPI" - No. 19; 2021 - P.78-82 7.Shklyaruk S. G. Financial risk management: a textbook. / Shklyaruk S. G. - Kyiv: SE "Publishing house "Personnel" - 2019 - 494 p. 8.Schmidt; A. V. Theory of financial management of enterprises / A. V. Schmidt. – Kyiv: Publishing House “Finance of Ukraine”; 2019. – 260 p